FORESIGHT AS A TOOL OF TECHNOLOGICAL PLANNING IN THE MANAGEMENT OF PUBLIC JOINT STOCK COMPANY “GAZPROM” IN THE ERA OF DIGITALIZATION - V. V. Degtyareva; D. A. Lozhnikova (Вестник университета)
The issues of presenting the basic prerequisites for forecasting and planning tools for managing an organization based on the foresight method, – have been highlighted. The strategic planning mechanism of PJSC Gazprom has been described, the place of foresight research in the formation of a long-term strategy has been reflected, and interaction with the innovation environment has been reflected. Five stages of foresight research and their filling have been presented. The sequence of stages of foresight research has been described. A generalized picture of collecting the necessary information for conducting a foresight study and forming a pool of experts from the preliminary registry on thematic selected areas has been presented. A list of criteria for assessing the prospects of technologies, as well as the sequence of their selection in accordance with the system of prospects indexes of technological developments for further updating the organization’s strategy, – has been considered. A graphical model of the results of technology assessment for their use in the strategic planning of the organization. A digital model that makes a decision on the choice of the necessary technologies based on semantic analysis of big data – IFORA has been considered. A comparison of information input and applied methods has been made. When preparing the article, such research methods as analysis, synthesis, and generalization were used.